2020
DOI: 10.1002/jmri.27034
|View full text |Cite
|
Sign up to set email alerts
|

Right and left ventricular interactions, strain, and remodeling in repaired pulmonary stenosis patients with preserved right ventricular ejection fraction: A cardiac magnetic resonance study

Abstract: BackgroundRight ventricular dilation and dysfunction is a common long‐term complication in patients with repaired pulmonary stenosis (rPS). Additionally, abnormal right and left ventricular interactions have been reported in right‐sided heart defect after intervention, including in pulmonary stenosis.PurposeTo analyze ventricular strain, remodeling, and left and right ventricular interactions in rPS patients with preserved right ventricular ejection fraction (RVEF) compared with healthy children using cardiac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
2
7
1
Order By: Relevance
“…Nevertheless, they described normal values for myocardial strain in healthy subjects (GLS mean value was − 19.1 ± 4.1%) from the analyses of images acquired in a 1.5 T scanner (Magnetom Avanto, Siemens, Erlangen, Germany), while, in our study (GLS mean value was − 14.2 ± 2.5%), subjects were examined using a 3.0 T MR Discovery 750 scanner (GE Healthcare, Chicago, USA). Similarly, Wang et al [ 43 ] used the same scanner as us and reported a GLS of − 13.55 ± 3.28% for healthy volunteers. So, normal values for GLS probably depend on many parameters, including the vendor and the software.…”
Section: Discussionmentioning
confidence: 55%
“…Nevertheless, they described normal values for myocardial strain in healthy subjects (GLS mean value was − 19.1 ± 4.1%) from the analyses of images acquired in a 1.5 T scanner (Magnetom Avanto, Siemens, Erlangen, Germany), while, in our study (GLS mean value was − 14.2 ± 2.5%), subjects were examined using a 3.0 T MR Discovery 750 scanner (GE Healthcare, Chicago, USA). Similarly, Wang et al [ 43 ] used the same scanner as us and reported a GLS of − 13.55 ± 3.28% for healthy volunteers. So, normal values for GLS probably depend on many parameters, including the vendor and the software.…”
Section: Discussionmentioning
confidence: 55%
“…The degree of RV structural remodeling and functional adaptability has been demonstrated to be important determinants of functional capacity and survival in patients with CTEPH. RVESVI, RVMI and strain et al have been used as RV remodeling markers ( 22 , 23 ). Our finding is that both RV PDF and PRVo correlated, but in opposite directions, with the conventional remodeling parameters such as RVEF, RVESVI, RVMI, and global longitudinal strain.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive studies revealed that strain, correlating with IS and infarct mass, demonstrated independently prognostic values in AMI patients [ 16 , 30 34 ]. Interestingly, there has been no consensus on which parameter is more valuable in predicting ALVR.…”
Section: Discussionmentioning
confidence: 99%